2019
DOI: 10.1007/s11229-019-02414-3
|View full text |Cite
|
Sign up to set email alerts
|

Is choice blindness a case of self-ignorance?

Abstract: When subject to the choice-blindness effect, an agent gives reasons for making choice B, moments after making the alternative choice A. Choice blindness has been studied in a variety of contexts, from consumer choice and aesthetic judgement to moral and political attitudes. The pervasiveness and robustness of the effect is regarded as powerful evidence of self-ignorance. Here we compare two interpretations of choice blindness. On the choice error interpretation, when the agent gives reasons she is in fact wron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Our findings follow and build on a growing number of similar results showing that accepting false feedback about past choices influence future choices and behaviors (Johansson et al, 2014;Luo & Yu, 2017;Strandberg et al, 2018;Taya et al, 2014). Recently, Bortolotti and Sullivan-Bissett (2019), suggested two interpretations of the general choice blindness effect. They contrast a 'choice error' interpretation whereby choice blindness reveals that people can be mistaken about their previous choices, with a 'choice change' interpretation whereby choice blindness reveals that people can be manipulated into reversing their choices within minutes of first making them.…”
Section: Choice-induced Preference Change In Groupssupporting
confidence: 86%
“…Our findings follow and build on a growing number of similar results showing that accepting false feedback about past choices influence future choices and behaviors (Johansson et al, 2014;Luo & Yu, 2017;Strandberg et al, 2018;Taya et al, 2014). Recently, Bortolotti and Sullivan-Bissett (2019), suggested two interpretations of the general choice blindness effect. They contrast a 'choice error' interpretation whereby choice blindness reveals that people can be mistaken about their previous choices, with a 'choice change' interpretation whereby choice blindness reveals that people can be manipulated into reversing their choices within minutes of first making them.…”
Section: Choice-induced Preference Change In Groupssupporting
confidence: 86%
“…The development of better introspective access can be of great help in countering CB. Indeed, a lack of introspection, which is one of the primary explanations for CB, can be caused either by self-ignorance of our choices or ignorance of the mismatched outcomes [ 10 , 11 , 12 ]. In the first case, people do not have complete introspective access and fail in the self-assignment of their own choices [ 10 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals the difficulty participants face in detecting manipulations of their initial choices by an experimenter who replaced the picture participants had chosen with one they had not. Some authors have suggested that this effect could be the result of insufficient introspection [ 10 , 11 , 12 ] or an underestimation of the influence of environmental and situational factors [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations